Pengaruh Penambahan NaOH dan Ca(OH)2 Terhadap Penurunan Kadar Logam Berat (Fe) di Kolong Tambang 23 Desa Kimhin Kecamatan Sungailiat - Elgatania Dwi Apriastuti; Mardiah Mardiah; Janiar Pitulima (MINERAL, 2017)
Tin mining activity causes a lot of opening pit known as kolong in Bangka Island. Ecologically, kolong has function as retention reservoir that contain harmful acid water. Tin mining ex-pit potentially causes environment effects especially the quality and quantity of water contained heavy metal. One of kolong in Tambang 23 Kimhin Village of Sungailiat subdistrict contain a quite high of heavy metal of Fe in amount 2.18 mg/L that tested from the result of testing of Health Official Laboratorium of Bangka Regency. Therefore, this research conducted to decrease metal grade in the water kolong. This research focused based on metal grade of Fe value. Analysis conducted by counting the decrease of percentage of Fe metal grade. The method used in lowering metal grade was precipitation method using NaOH and Ca(OH)2 solution. Metal grade analysis used spectrophotometer. The aim of this research was to determine the influence of solution concentration, precipitation time and solution influence of NaOH and Ca(OH)2 in lowering Fe grade. The result of research showed the influence of adding precipitation of NaOH and Ca(OH)2 with the precipitation time. The longer time of precitipation, the bigger percentage of lowering Fe metal. The biggest percentage of Fe metal grade was on concentration of NaOH 6% and Ca(OH)2 3% with the lowering percentage of 88.99% and 96.33% respectively. The optimum time to precipitate Fe metal was in 60 minute. Based on research result showed that precitipation of NaOH better than Ca(OH)2.